Global energy scenarios and their implications for future shipped trade. (October 2017) - Sharmina, Maria; McGlade, Christophe; Gilbert, Paul; Larkin, Alice
Abstract: About half of the world's oil supply, a fifth of coal supply and a tenth of natural gas supply are traded by ship. Accordingly, any significant shift in the size and shape of the global energy system has important consequences for shipping, which underpins international trade and supports economic development. The Paris Agreement requires an acceleration of the drive towards energy system decarbonisation. Yet, the International Maritime Organisation's understanding of the future is more in line with the high-carbon scenarios analysed here. This paper is a first comprehensive and global assessment of implications of fundamental changes to global and regional energy systems for international shipping, under-researched in energy scenarios consistent with deep decarbonisation. It concludes that, despite uncertainties (particularly with negative emission technologies), fossil fuel trade by the middle of the century will almost certainly be significantly lower under low-carbon than under high-carbon scenarios, and (for oil and coal) lower than in 2012. As to bioenergy and captured carbon dioxide, while their supply is expected to increase during a low-carbon transition, worldwide shipped trade in these commodities will not necessarily grow, based on the analysis in this paper. In other words, if the low-carbon futures envisioned in the Paris Agreement materialise, energy-related shipping will likely decline (by a quarter for oil and by 50% for coal in the median < 2 °C scenarios by 2050), with significant ramifications for policies and regulation in the shipping sector and international trade. Highlights: Implications of energy system change for global shipping are significant. Fossil fuel trade by 2050 is lower under low-carbon scenarios than in 2012. Fossil fuel trade by 2050 is much lower in low-carbon than in high-carbon scenarios. Bioenergy and CO2 trade might not grow to compensate for lower fossil fuel trade. Potential energy-shipping decline under Paris Agreement should spur strategic planning.